If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9m + -12 = 8 + -4m Reorder the terms: -12 + -9m = 8 + -4m Solving -12 + -9m = 8 + -4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4m' to each side of the equation. -12 + -9m + 4m = 8 + -4m + 4m Combine like terms: -9m + 4m = -5m -12 + -5m = 8 + -4m + 4m Combine like terms: -4m + 4m = 0 -12 + -5m = 8 + 0 -12 + -5m = 8 Add '12' to each side of the equation. -12 + 12 + -5m = 8 + 12 Combine like terms: -12 + 12 = 0 0 + -5m = 8 + 12 -5m = 8 + 12 Combine like terms: 8 + 12 = 20 -5m = 20 Divide each side by '-5'. m = -4 Simplifying m = -4
| -4y^2-19y-5=0 | | 7p-4=12-3p | | X-18=-50 | | 5x^2-9=16 | | 6z-2=4z+12 | | 1.4x-13=-15 | | y=x^2+16x+5 | | 11x=59 | | 10.16=4r | | y-2x^2+8=0 | | .15x^4+32.69x-2000=0 | | 2x-8=32-2x | | hy-2x^2+8=0 | | 7x-55=12x | | 21+4(2n-11)=1 | | -3y-15=2(17-5y) | | 3x-10=9x | | 10y=9(y+13) | | 2X-15=83 | | 3(4-2.25x)=25 | | 4x+15-3x=-8-11 | | -8-12=4x+18-3x | | 13x-8=14x | | 8y+4=7(y-1) | | y=(x^2)(sinx)(tanx) | | 5-(4-9)= | | -8x+4+9x=-13+3 | | 6z^2-37z-553=0 | | 3x+5=175 | | y+4.4=-7.7-8.2 | | 10-3x=-5k | | 4x^2-44=1835 |